2006
DOI: 10.4049/jimmunol.177.1.414
|View full text |Cite
|
Sign up to set email alerts
|

A Role for DNA Hypomethylation and Histone Acetylation in Maintaining Allele-Specific Expression of Mouse NKG2A in Developing and Mature NK Cells

Abstract: The repertoire of receptors that is expressed by NK cells is critical for their ability to kill virally infected or transformed cells. However, the molecular mechanisms that determine whether and when NK receptor genes are transcribed during hemopoiesis remain unclear. In this study, we show that hypomethylation of a CpG-rich region in the mouse NKG2A gene is associated with transcription of NKG2A in ex vivo NK cells and NK cell lines. This observation was extended to various developmental stages of NK cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
(50 reference statements)
2
14
0
Order By: Relevance
“…The half-and-half pattern of DNA methylation correlates with the mono-allelic expression of Ly49A, C and NKG2A as was subsequently shown using F1 hybrids for Ly49a and Nkg2a (22,44). If DNA methylation does not correlate with stochastic mono-allelic expression; either stochastic gene expression is maintained at the level of histone modifications only or this pattern is possibly an indication of high, if not complete, bi-allelic expression and even the lack of stochastic expression of the activating receptors.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The half-and-half pattern of DNA methylation correlates with the mono-allelic expression of Ly49A, C and NKG2A as was subsequently shown using F1 hybrids for Ly49a and Nkg2a (22,44). If DNA methylation does not correlate with stochastic mono-allelic expression; either stochastic gene expression is maintained at the level of histone modifications only or this pattern is possibly an indication of high, if not complete, bi-allelic expression and even the lack of stochastic expression of the activating receptors.…”
Section: Discussionmentioning
confidence: 56%
“…We have shown that DNA methylation of this region correlates with expression patterns of these receptors as with the inhibitory Ly49A, Ly49C (22) and NKG2A (44). Furthermore, as in the case of Ly49a , the CpG dinucleotides downstream of the transcriptional start site of Ly49h seem to have higher levels of methylation compared to those located upstream in Ly49H-negative cells.…”
Section: Discussionmentioning
confidence: 96%
“…About 60% of human genes contain PCIs [9], most of which are unmethylated [11], [12]. Such PCIs are more common in widely-expressed (housekeeping) genes [13], supporting the view that non-methylated PCIs actively maintain gene transcription [14], [15].…”
Section: Introductionmentioning
confidence: 86%
“…4A). A promoter region of the housekeeping gene Hprt was amplified as an example of an active gene, and a GC-rich region of the NK cell-specific gene Nkg2a, which is deacetylated in nonexpressing cells (50), was amplified as an example of an inactive gene.…”
Section: Potential Explanations For Higher Levels Of Etnii Than Musd mentioning
confidence: 99%